(untitled) (Altre Modernità, 2012)
The objective of this work is to develop a reflection on the meaning of psychoanalysis material proposed by Bachelard in poetic side of his work. We will seek to show, throughout development, that the meaning of the term psychoanalysis is totally different in two aspects: epistemological and poetic. This is because in epistemology, Bachelard exalts psychoanalysis as a method, while in poetry, criticizes the intensive Freudian psychoanalysis, showing that, due to its therapeutic purpose, fails to grasp the picture and dream of themselves, but rather rationalizes the . The text will become evident that only psychoanalysis material that leads to an area on the intimacy of the matter may result in the production of images and dreams whose dynamism leads to better understanding of the human spirit.